1987
DOI: 10.1007/bf01907067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac and hemodynamic effects of plateletactivating factor-acether and leukotriene D4 in anesthetized dogs

Abstract: In anesthetized dogs, platelet-activating factor-acether (PAF; 0.2-1.6 micrograms/kg) and leukotriene (LT) D4 (0.5, 1, and 3 micrograms/kg) were injected into the left circumflex (LCX) coronary artery. Cardiac and systemic hemodynamics, and the ECG were continuously recorded. PAF reduced cardiac performance and affected hemodynamics in a dose-dependent manner: At 7 +/- 3s, LCX flow initially increased by 40%-172% followed by a reduction of 43%-100%, and coronary diameter (measured with ultrasonic techniques) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In previous studies, the leukotriene antagonist FPL-55712, was shown to attenuate the vasocons-C4 and LTD4 trictor response following injections of PAF (Feuerstein et al., CM FR-900452. 1984;Piper & Stewart, 1986;Fiedler et al, 1987). However, not affect the the vasodilator effect, when observed, was not altered by FPL-)Opmol LTC4 55712 (Feuerstein et al, 1984;Fiedler et al, 1987 (Piper & Stewart, 1986; us to examine Man et al, 1990) ts, Specific binding of radiolabelled PAF was first demonn the coronary strated in platelets (Valone et al, 1982;Hwang et al, 1983) and subsequently demonstrated in a number of tissues (see review of Braquet et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the leukotriene antagonist FPL-55712, was shown to attenuate the vasocons-C4 and LTD4 trictor response following injections of PAF (Feuerstein et al., CM FR-900452. 1984;Piper & Stewart, 1986;Fiedler et al, 1987). However, not affect the the vasodilator effect, when observed, was not altered by FPL-)Opmol LTC4 55712 (Feuerstein et al, 1984;Fiedler et al, 1987 (Piper & Stewart, 1986; us to examine Man et al, 1990) ts, Specific binding of radiolabelled PAF was first demonn the coronary strated in platelets (Valone et al, 1982;Hwang et al, 1983) and subsequently demonstrated in a number of tissues (see review of Braquet et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed a biphasic effect, i.e. an increase in flow followed by a decrease in flow, after intracoronary injection of PAF (Feuerstein et al, 1984;Mehta et al, 1986;Erza et al, 1987;Fiedler et al, 1987). In a previous study, we demonstrated that depending on the dose, bolus injections of PAF could produce vasodilator (10fmol-1 pmol PAF), vasoconstrictor (1 nmol PAF) or a biphasic response (10 and 100pmol PAF) in rat perfused hearts (Man et al, 1990).…”
Section: Introductionmentioning
confidence: 95%
“…Inhibitors Control (n = 12) IM, (n = 6) (2 mg kg-) VAP, (n = 7) (100 Mg kg') AA-861, (n=7) (5 mg kg-') L-NAME, (n = 6) (5 mg kg-l) TCV-309, (n = 5) (300 pg kg') (Fiedler et al, 1987). Also, PAF itself had direct negative inotropic effects (Tamargo et al, 1985;Robertson et al, 1988 (Toyofuku et al, 1988;Yamanaka et al, 1992), and leukotrienes (Piper & Stewart, 1986) in response to exogenous PAF have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…PAF has been detected in the effluent blood from the coronary sinus in patients with coronary artery disease undergoing atrial pacing (Montrucchio et al, 1986) and release of PAF from ischaemic-reperfused rabbit heart has been demonstrated (Montrucchio et al, 1989). The effects of PAF in the coronary circulation have been shown in a number of in vivo (Levi et al, 1984;Piper & Stewart, 1986;Man et al, 1990) and in vitro studies (Feuerstein et al, 1984;Jackson et al, 1986;Mehta et al, 1986;Ezra et al, 1987;Fiedler et al, 1987).…”
Section: Introductionmentioning
confidence: 99%